2013
DOI: 10.1002/ana.23858
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates in an experimental model of repetitive mild brain injury

Abstract: Within the vulnerable time period between injuries, rmTBI produces long-term cognitive deficits independent of increased amyloid β or tau phosphorylation. In this model, cognitive outcome is not influenced by APOE4 status. The data have implications for the long-term mental health of athletes who suffer multiple concussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(193 citation statements)
references
References 50 publications
9
181
2
1
Order By: Relevance
“…[65][66][67][68][69] Increasing amounts of head movement have also been incorporated, [70][71][72] to more closely approximate human head kinematics following mTBI. 73 As such, WD models are increasingly utilized to model repeated mTBI.…”
Section: Closed-head Models Of Tbimentioning
confidence: 99%
See 2 more Smart Citations
“…[65][66][67][68][69] Increasing amounts of head movement have also been incorporated, [70][71][72] to more closely approximate human head kinematics following mTBI. 73 As such, WD models are increasingly utilized to model repeated mTBI.…”
Section: Closed-head Models Of Tbimentioning
confidence: 99%
“…54,56,65,70 One repeated mTBI study reported significant acute neuronal death in the entorhinal cortex and around hemorrhagic lesions, following 5 CCI mTBI given at 24 h intervals. 150 Findings were deemed an outcome of both injury number and inter-injury interval, as a 48-h interval prevented neurodegeneration 150 ; however, a study using similar injury parameters and experimental design did not report neurodegenerative changes.…”
Section: Cell Death Following Repeated Mtbimentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that animal models of repetitive concussive brain injury have shown a decrease in cognitive function in the absence of such potential confounding variables. [55][56][57] "Second impact syndrome" is a term used to describe a devastating brain injury associated with cerebral edema that occurs after an often minor blow to the head is sustained before full recovery from a concussion. [58][59][60][61] Although second impact syndrome is often associated with football, it has been observed in other sports, such as ice hockey, boxing, and skiing.…”
Section: Cumulative and Catastrophic Head And Neck Injuries In Footballmentioning
confidence: 99%
“…In recent years, there has been an increase in the number of military personnel exposed to traumatic head injury, leading the Department of Defense to designate TBI as the signature injury of the troops serving in Iraq and Afghanistan (Hoge et al, 2009). The nonspecific nature of TBI symptomatology (Darwish et al, 2012;Mannix et al, 2013), compounded by the variable presentation of TBI, has made the diagnostic and prognostic approach challenging. Not surprisingly, considerable effort has been directed toward identifying a panel of peripheral blood markers reflective of the severity of brain injury.…”
Section: Introductionmentioning
confidence: 99%